Chemistry Storytelling with AI: A Descriptive Research of Ebook Creation for Grade 10 Students - Nugraha, Christophorus Ardi; Harsono, Rita Jhon (JKTP: Jurnal Kajian Teknologi Pendidikan, 2024)
Teaching chemical compounds in an interesting way is quite challenging because of the complexity of the material and the difficulty of contextualizing various chemical elements in everyday life. This study explores the use of AI tools and storytelling to design engaging chemistry lessons for tenth grade students. Conducted at Bandung Alliance Intercultural School, the project involved fifteen students who created ebooks to teach chemical compounds to second graders. AI tools like ChatGPT, Gemini, and CanvaAI facilitated brainstorming, storyline development, and image generation, while human input ensured the content was age-appropriate and engaging. The collaborative nature of the project fostered student ownership and engagement. Data were collected through observations and rubric scoring. Findings indicate that AI-enhanced storytelling can make chemistry lessons more interactive and relatable. However, the study's generalizability is limited due to its single-school setting. Future research should replicate this method in diverse educational environments and use experimental designs to measure the effectiveness of AI and storytelling in chemistry education. Abstrak Mengajarkan senyawa kimia secara menarik itu cukup menantang karena kompleksitas materi dan sulitnya mengkontekstualisasi berbagai unsur kimia dalam kehidupan sehari-hari. Penelitian ini mengeksplorasi penggunaan alat AI dan metode bercerita untuk merancang pembelajaran kimia yang menarik bagi siswa kelas sepuluh. Penelitian ini dilakukan di Bandung Alliance Intercultural School, melibatkan lima belas siswa yang membuat ebook untuk mengajarkan senyawa kimia kepada siswa kelas dua. Data dikumpulkan melalui observasi dan penilaian rubrik. Alat AI seperti ChatGPT, Gemini, dan CanvaAI digunakan untuk mencari ide cerita, mengembangkan alur cerita, dan membuat gambar. Intervensi dari siswa diperlukan untuk memastikan kontennya sesuai usia dan menarik. Sifat kolaboratif proyek ini mendorong kepemilikan dan keterlibatan siswa. Temuan menunjukkan bahwa metode bercerita yang diperkaya dengan AI dapat membuat pelajaran kimia lebih interaktif dan relevan. Sayangnya, generalisasi hasil penelitian ini terbatas karena dilakukan di satu sekolah saja. Penelitian selanjutnya harus mereplikasi metode ini di lingkungan pendidikan yang beragam dan menggunakan desain eksperimental untuk mengukur efektivitas AI dan metode bercerita dalam pendidikan kimia.